Detection of M. tuberculosis Using Cartridge-Based Technology in Patients with Negative Sputum Microscopy Results in a Regional Laboratory - P. I. Eliseev; E. I. Nikishova; A. Yu. Krupskaya; V. I. Shtraukh; E. S. Khimova; A. O. Maryandyshev (Туберкулез и болезни лёгких)
The objective: to evaluate results of M. tuberculosis detection and testing drug susceptibility to rifampicin using molecular genetic methods in tuberculosis patients with a negative sputum smear microscopy result.Subjects and Methods. Pulmonary tuberculosis patients registered in Arkhangelsk Region from 2016 to 2020 were enrolled in the study; those patients were notified as new cases and relapses with a negative sputum smear microscopy result before treatment and had results of molecular genetic testing (MGT) (Xpert MTB/RIF MTB/RIF) and BACTEC MGIT 960 available.Results. 479 people (40%) were registered as pulmonary tuberculosis cases with a negative sputum smear microscopy result. MGT was performed in 327 (68%) patients. A positive result of MGT was received in 120 (37%) patients, a positive result of BACTEC MGIT 960 was received in 165 (50%) people. Concordance of results was observed in 70% of cases. In 136 (41%) people, both tests did not detect Mycobacterium tuberculosis, in 95 (29%) both tests showed a positive result. Discrepancies between the results of two tests were observed in 30% of cases. In 71 (22%) cases, culture growth was observed in BACTEC MGIT 960 with negative results of MGT. In 8% of cases, DNA of Mycobacterium tuberculosis was detected, but there was no culture growth on the nutrient medium. 43/120 (36%) cases of resistance to rifampicin were detected. The median time from sputum collection to initiation of MDR-TB treatment based on sputum MGT results made 18 (IQR 10–29) days. Molecular genetic testing makes it possible to promptly detect the majority of TB patients with a negative sputum smear result, and reduce the time for drug susceptibility testing, which allows this testing to be used as the first test when examining for pulmonary TB.